Chapter 4 - Sustainable Waste Management Practices: Challenges in the Republic of Macedonia - Toshevska trpchevska, Katerina; Kikerkova, Irena; Makrevska disoska, Elena (Emerald Publishing Limited, 2017)
The paper has a special focus on managing packaging and packaging waste and analyzes the results of the implementation of the Law of Management of Packaging and Packaging Waste which was enforced in 2009. Positive initiatives in waste management practices were undertaken by PAKOMAK, the first Macedonian company that has been holding the license for selecting and processing of packaging waste since January 2011. The company has a proactive role in promoting the importance of packaging waste and its management, with a special emphasis on projects that increase the awareness of the whole society, especially that of the young population. Some of the projects that increase the eco-awareness of young population will be presented in the paper.
Green economy in the Western Balkans
Keywords: Republic of Macedonia; waste management; packaging; education; young population